MiR-125b inhibits cardiomyocyte apoptosis by targeting BAK1 in heart failure - Bei Zhang; Shanyong Mao; Xingde Liu; Sha Li; Haiyan Zhou; Ying Gu; Wupeng Liu; Lei Fu; Chunyan Liao; Pengzhen Wang (BMC, 2021)
Abstract Background Although miR-125b plays a crucial role in many human cancers. However, its function in heart failure (HF) remains unclear. Our study aimed to investigate its involvement in heart failure. Methods In this study, the mouse HF model was successfully constructed through transverse aortic constriction (TAC) operation. Changes in mRNA and protein levels in isolated myocytes and heart tissues were examined using qRT-PCR, Western blot and Immunohistochemical staining and immunofluorescent staining. Changes in cardiac functions were examined using ultrasound. Interactions between miR-125b and BAK1 was analyzed using the luciferase reporter assay. Cardiomyocyte apoptosis was evaluated using the TUNEL staining. Results We found that miR-125b expression was significantly downregulated in myocardial tissues of HF mice. Moreover, miR-125b upregulation in HF mice injected with agomir-125b efficiently ameliorated cardiac function. Further, miR-125b upregulation significantly decreased the protein levels of apoptosis-related makers c-caspase 3 and Bax, while increased Bcl-2 expression. In addition, BAK1 was identified as a direct target of miR-125b. As expected, BAK1 overexpression observably reversed the effect of agomir-125b on cardiac function and on the expression of apoptosis-related makers in the heart tissues of HF mice. Conclusions Taken together, miR-125b overexpression efficiently attenuated cardiac function injury of HF mice by targeting BAK1 through inhibiting cardiomyocyte apoptosis, suggesting that miR-125b/BAK1 axis might be a potential target for the diagnosis or treatment of HF.